LEARNING TRANSLATION METHODS: STUDY ANALYSIS OF TOURISM BROCHURE "INSPIRATION OF HISTORICAL HERITAGE" - Nasution, Dewi Kesuma; Kharisma, Adib Jasni (Jurnal As-Salam, 2024)
English students who focus on tourism translation face unique challenges that require special methods in practice. Tourism translation requires specific methods in practice. This study aims to investigate translation methods applied in the English translation of the Tourism Brochure ’Borobudur: Inspiring Historical Heritage’ and identify the most frequent and least frequent translation methods in the brochure ’Borobudur: Inspiring Historical Heritage’. The results of the analysis discovered that the most frequent method used is equivalence (28%), followed by adaptation (19%), transposition (17%), modulation (16%), calque (11 %), and borrowing (9%). The equivalence method is applied because the source text is reformulated as necessary to give the reader an impression of the text’s naturalness. Adaptation is used to adapt the culture in the target text. In the meantime, transposition is used to replace the word class to make it efficient. Modulation is used to change the form of the message. Calque is used for phrases that need no major replacement of the structure and word choices. Borrowing is used when the source text has no proper translation in the target text. Therefore, English students studying tourism translation require unique learning methods that include aspects of language, culture, and technology. By integrating this approach, students can comprehensively prepare themselves to become quality tourism translators responsive to the dynamics of the global tourism industry.